2021
DOI: 10.1186/s12917-021-03077-4
|View full text |Cite
|
Sign up to set email alerts
|

Signature selection analysis reveals candidate genes associated with production traits in Iranian sheep breeds

Abstract: Background Sheep were among the first animals to be domesticated. They are raised all over the world and produce a major scale of animal-based protein for human consumption and play an important role in agricultural economy. Iran is one of the important locations for sheep genetic resources in the world. Here, we compared the Illumina Ovine SNP50 BeadChip data of three Iranian local breeds (Moghani, Afshari and Gezel), as a population that does not undergone artificial breeding programs as yet,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 85 publications
1
23
0
Order By: Relevance
“…The pattern of LD decay can provide valuable insights into population history, including breeding systems and evolution of a population [42][43][44]. In this study, the LD values among SNPs decreased with increasing physical distance, which is in accordance with studies on different livestock species [42,45]. The relatively low levels of LD in the entire genome of cross-bred animals are probably the result of past admixture events between Red-Angus and Mongolian cattle that have been experienced due to genetic improvement of local cattle breeds for meat production traits.…”
Section: Genetic Diversity and Population Structuresupporting
confidence: 88%
“…The pattern of LD decay can provide valuable insights into population history, including breeding systems and evolution of a population [42][43][44]. In this study, the LD values among SNPs decreased with increasing physical distance, which is in accordance with studies on different livestock species [42,45]. The relatively low levels of LD in the entire genome of cross-bred animals are probably the result of past admixture events between Red-Angus and Mongolian cattle that have been experienced due to genetic improvement of local cattle breeds for meat production traits.…”
Section: Genetic Diversity and Population Structuresupporting
confidence: 88%
“…This method is beneficial because it does not necessitate the availability of phenotypic records and may detect selection signals even when long‐term human‐mediated selection for wool qualities has resulted in total fixation of the desirable allele (Megdiche et al, 2019). Mohamadipoor Saadatabadi et al (2021) applied F ST and nucleotide diversity‐based statistical approaches to identify selection signals in genomic areas under selection pressure in three Iranian sheep breeds. The research revealed potential genes that regulate crimps in wool ( KRTAP20‐2 , PTPN3 , and NBEA genes), fiber fineness ( PIK3R4 gene), and the development of hair follicles ( LHX2 gene).…”
Section: Selection Signature Studies In Fiber‐producing Animalsmentioning
confidence: 99%
“…The most drought-affected regions of the Fertile Crescent are located in Iraq and Iran, which are also part of the hot-arid region of the Afro-Asian desert belt ( Ashraf et al, 2021 ; Kaniewski et al, 2012 ). As a result, indigenous domesticated animals of the region are well adapted to the local hot-desert environment ( Al-Thuwaini et al, 2019 ; Asadollahpour Nanaei et al, 2022 ; Saadatabadi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%